EVALUATION OF COMPLETE FEED BASED ON PALM KERNEL CAKE PORTIFIED WITH PROBIOTICS ON RUMEN FERMENTABILITY: EVALUASI PAKAN KOMPLIT BERBASIS BUNGKIL INTI SAWIT YANG DI PORTIFIKASI PROBIOTIK TERHADAP FERMENTABILITAS RUMEN - Raguati, Raguati; Afzalani; Muthalib, RA; Dianita, Rahmi; Fitri, Ega (Jurnal Peternakan Nusantara, 2024)
This research aimed to evaluate complete feed formulas with palm kernel meal (BIS) levels in concentrates fortified/enriched with probiotics on rumen fermentability. The material used is complete animal feed. The feed consists of forages (elephant grass, palm frond leaves) and concentrates (tofu dregs, fine corn, bran, palm kernel meal). 1% probiotics. In vitro analysis equipment, namely analytical scales, test tubes, oven, gauze, water bath, centrifuge, flask, filter, gauze, incubator, pipette dispenser, pH meter and Buchi brand rotary evaporator, flask, spectrometer, beaker glass, distillation tube, phenolphthalein, dropper pipette, Erlenmeyer flask, Conway cup. The materials used were rumen fluid, McDougall’s solution, supernatant, 0.5 N NaOH, Vaseline, saturated Na2CO3, alcohol, 1 ml boric acid solution (0.005 N H2SO4), distilled water, 0.5 N HCl. This research used a Completely Randomized Design (CRD) consisting of 5 treatments and 5 replications. P0: 60% Forage (50% elephant grass + 50% palm fronds)/HPR + 40% concentrate (50% bran, 30% fine corn, 20% tofu dregs)/Const. + 0% BIS + 0% probiotics. P1: (HPR + Const) + 0% BIS + 1% probiotics. P2: (HPR + Const) + 10% BIS + 1% probiotics. P3: (HPR + Const.) + 20% BIS + 1% probiotics. P4: (HPR + Const.) + 30% BIS + 1 % probiotics. The variables observed were dry matter digestibility (KcBK), organic matter digestibility (KcBO), metabolic energy (EM), microbial protein production (PPM), and total VFA. Data were analyzed using variance (ANOVA) and if there was a significant effect, Duncan’s further test was carried out. The results showed that complete feed based on palm kernel meal enriched with probiotics had a significant effect (P<0.05) on KcBK, KcBO, EM and PPM and had no significant effect (P>0.05) on the VFA value. Average KcBK 24.84-29.05%, KcBO 20.49-25.52%. EM 9.09-9.96 KCal, PPM 130.18 – 166.75mg/g, and VFA value 1.15-1.24 mM. This research concludes that using palm kernel meal up to 30% ported with probiotics in complete feed positively affects rumen fermentability in vitro